The derivative of `f(x) = (e^(2x) - 2)/(1 - e^x)` has to be determined. Use the quotient rule.

f'(x) = `((e^(2x) - 2)'(1 - e^x) - (e^(2x) - 2)(1 - e^x)')/(1 - e^x)^2`

= `(2*e^(2x)(1 - e^x) - (e^(2x) - 2)(- e^x))/(1 - e^x)^2`

= `(2*e^(2x) - 2*e^(3x) + e^(3x) - 2e^x)/(1 - e^x)^2`

= `(2*e^(2x) - e^(3x) - 2e^x)/(1 - e^x)^2`

= `(e^x*(2e^x - e^(2x) - 2))/(1 - e^x)^2`

**The derivative of `f(x) = (e^(2x) - 2)/(1 - e^x) ` is **`f'(x) = (e^x*(2e^x - e^(2x) - 2))/(1 - e^x)^2`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now